Antihypertensive Effect of Ethanolic Extract from Acanthopanax sessiliflorus Fruits and Quality Control of Active Compounds. (23rd April 2018) - Jung, In Ho; Kim, Sung Eun; Lee, Yeong-Geun; Kim, Dae Hyun; Kim, Haneul; Kim, Geum-Soog; Baek, Nam-In; Lee, Dae Young
Abstract : Acanthopanax sessiliflorus (Rupr. & Maxim.) Seem., which belongs to the Araliaceae family, mainly inhabits Korea, China, and Japan. Traditionally, Acanthopanax species have been used as treatment for several diseases such as diabetes, tumors, and rheumatoid arthritis. Especially, its fruits have many biological functions including antitumor, immunostimulating, antithrombosis, and antiplatelet activities. Recently, the extract of A. sessiliflorus fruit has been reported to have antithrombotic and antiplatelet activities related to the alleviation of hypertension. Therefore, we investigated the antihypertensive effect of ethanolic extract from A. sessiliflorus fruits (DHP1501) through in vivo, ex vivo, and in vitro studies. In this study, DHP1501 demonstrated free radical scavenging capacity, enhanced endothelial nitric oxide (NO) production, and inhibited angiotensin-converting enzyme (ACE) activity in spontaneously hypertensive rats (SHRs), resulting in the improvement of vascular relaxation and decrease in blood pressure in the hypertensive animal model. These results suggest that A. sessiliflorus fruit extract may be a promising functional material for the prevention and treatment of hypertension. Furthermore, this study demonstrated the utility of MS-based active compounds for the quality control of DHP1501.